An Inappropriate Preface to End a Seminar in Honour of Bedřich Loewenstein - Šmahel, František (Dějiny – teorie – kritika, 2009)
The author approaches Loewenstein’s Víra v pokrok (Faith in Progress) from the perspective of an historian and researcher for whom the construction of history takes preference over reflections on it. As a mediaevalist he focuses on the starting points of Loewenstein’s book and the European idea of progress – namely, Christian ‘soterial’ history. The author relativizes the often schematic linking together of the ideas of Modernity and novelty, which began with the Modern Age. And using several examples, the focus of which is in the cultural milieu of the court of Charles IV, he demonstrates the use of their terms, meanings, and functions in the world of Late Mediaeval man.